Description of Workforce Preparedness for Fire Management at Dinoyo Health Center - Fresvian Jenrivo; Ani Asriani Basri; Fariz Zuvil Arganata; Zanuba Syifa' Qotrunnada (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Background: Dinoyo Community Health Center is a health facility in Malang City that must implement fire safety. There have been 4 incidents in 2020 and 8 incidents in 2021 where fire occurred at community health centers. Preparedness is carried out as an effort to deal with fires from a human perspective. Research objective: To determine workforce preparedness for fire management at the Dinoyo Community Health Center. Research type: descriptive quantitative with a population of 55 people using saturation sampling techniques. There are 2 preparedness parameters in this research variable, namely knowledge and attitudes. Results: The preparedness of the workforce is "ready" category for fire management with an index value of 76.10. The level of knowledge scored 66.23 is "ready" category and attitude scored 85.98 is "very ready" category. Conclusion: The attitude value is higher than the knowledge value. This is because attitudes are not only influenced by knowledge, but also influenced by personal experience, the influence of other people, and emotional influence. The workforce has received fire management training and simulations. The interview results show that the workforce understands information related to emergencies. Suggestion: Workers should increase their knowledge through print media or the internet.